The Mahanubhavs - Rigopoulos, Antonio (Studi e saggi, 2005)
The ascetic, devotional sect of the Mahanubhavs -Those of the greatexperience - arose, like the much more popular bhakti movement ofthe Vårkaris centred in Pandharpur, in thirteenth century Maharastra.If in the beginning the Mahanubhavs had a fairly rapid expansion, especiallyin the northern and eastern regions of Maharastra, around theend of the fourteenth century their movement went underground aimingat a defensive isolation from the larger Hindü context. They centredthemselves in remote areas and villages. Although the prominentleaders among the early Mahanubhavs were brahma's (often convertsfrom the prevailing advaita vaißñavism), their followers were and aremostly non-brahma's, that is, low caste people and even untouchables.Outside of their own closed circles Mahanubhavs were met with prejudiceand distrust, at least up to the beginning of the twentieth century.In this volume the author offers an overview of the origins and mainreligious and doctrinal characteristics of the Mahanubhavs, discussingthose aspects which appear especially revealing of their differenceand nonconformity.